Apomorphine infusion in advanced Parkinson disease. Issue 12 (December 2018) - Antonini, Angelo; Jenner, Peter
The TOLEDO study provides new evidence to support the use of subcutaneous apomorphine infusion to control motor fluctuations in patients with advanced Parkinson disease. The findings should encourage neurologists to consider implementing apomorphine infusion or other device-aided therapies earlier in the disease course, before the emergence of troublesome dyskinesias.